A formação de estudantes de educação social para a ética prática: alguns desafios - François Gillet (Escola Superior de Educação de Paula Frassinetti, 2011)
This communication aims to present a research work done collaboratively by several training centers for childcare work in Europe. The project is finishing at this very moment I'm writing (late 2000) its second year, but it shall be extended for at least other two years. Therefore, here we are dealing with the first part of the project. It is important to understand that this is a true team effort that has been organized spontaneously without any external proposal.